The analysis of students’ reading and writing difficulties in learning english at universitas kristen indonesia - Lamhot Naibaho (Jurnal Konseling dan Pendidikan, 2022)
This study aims to analyse the students' reading and writing difficulties in learning English, and it was conducted at Universitas Kristen Indonesia. The design of this study is a quantitative study with a survey design. The study data were collected by distributing the questionnaire to 80 students of Universitas Kristen Indonesia. The study instrument covered the students' background, reading difficulties, writing difficulties, and perceptions of their lecturers' teaching. The data of the study were analysed using SPSS 7.5. The weakness of students in mastering reading and writing ability affects their potential and motivation in mastering various other skills in the English language. The study results showed that all respondents agreed that the factors of ability and creativity of lecturers could change the perception and awareness that they also have the potential to succeed in learning. Then it is concluded that in a collaboration involving the school management, it is hoped to build a conducive school climate, and a safe school environment can stimulate motivated students to continue learning.